Peran BUMDes Desa Candiwates Dalam Meningkatkan Perekonomian Masyarakat Melalui Pasar Jande - Musyayadah, Rizqiyatul; Adi, Khofifatu Rohmah; Idris, Idris (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
BUMdes in Candiwates Village in collaboration with the community built a business unit called Pasar Jande (ndeso snacks). Pasar Jande (jajanan ndeso) which is sheltered by BUMdes Candiwates was only built in 2018, a market that sells traditional snacks with a modern place and feel. The purpose of this study is to analyze the role of BUMDes and analyze the supporting and driving factors and obstacles in improving the community's economy through Jande Market. This research is a descriptive qualitative research, with data collection techniques through observation, interviews and documentation. Meanwhile, the data analysis technique using the Miles, Huberman and Saldana analysis model includes data collection, data condensation, data presentation and verification/conclusion. The results showed that the role of BUMDes Candiwates through Pasar Jande succeeded in creating jobs by involving the community through mothers to entrust their snacks and youths who worked as waiters at Jande Market. The role of BUMDes can run well because of good coordination between management, members and the community, supportive views, diverse snacks and good service are supporting internal factors, and external factors come from the availability of land used to build Jande Market. Meanwhile, the internal factor that hinders it comes from the pessimism of the community because the location of Jande Market is far from the main road and the external factor comes from the erratic weather.